Analisis Korelasi Antara Inflasi dan Pertumbuhan Ekonomi Di Sumatera Utara - Suci Frisnoiry; Nurul Masita; Gustia Louisa Nainggolan; Nia Fadilla (STEKOM PRESS, 2024)
This research aims to measure the strength of the correlation between inflation and economic growth in North Sumatra. Employing a quantitative methodology based on primary data obtained from the website sumut.bps.go.id. Inflation does not significantly affect economic growth, according to data analysis using tests for determination, correlation coefficients, simple linear regression, and partial testing (t tests). Since the probability value is not statistically significant (0.139>0.05), we may conclude that H1 is not valid. This means that there is not enough evidence to say that inflation has a significant impact on economic growth. In addition, the low correlation between inflation and economic growth indicates a weak relationship between the two variables. It can be said that the research results show that the inflation rate does not have a significant correlation with the rate of economic growth.